Big Bang Nucleosynthesis and Recombination - Năstase, Horaţiu [UNESP] (My University, 2019)
In this chapter we will describe Big Bang Nucleosynthesis (BBN), the combination of fundamental protons and neutrons into nuclei, as well as calculate more precisely the temperature of recombination.